Effects of neuroleptics and antidepressants on the cardiovascular system: literature review - V. Rutkauskas (Neurologijos seminarai, 2019)
Antidepressants and neuroleptics used to treat mental disorders can cause significant and potentially fatal cardiovascular problems. It is important to evaluate the patient’s cardiovascular risk and consider it before choosing and prescribing the most appropriate drug. This review provides literature data on the adverse effects of neuroleptics and antidepressants on the cardiovascular system. The emphasis is put on their effects on arterial blood pressure, electrophysiological changes, and risk of provoking cardiac muscle and coronary artery diseases.